The clinical phenotype of YWHAE‐NUTM2B/E positive pediatric clear cell sarcoma of the kidney. Issue 2 (6th November 2015) - Gooskens, Saskia L.; Kenny, Colin; Lazaro, Antonio; O'Meara, Elaine; van Tinteren, Harm; Spreafico, Filippo; Vujanic, Gordan; Leuschner, Ivo; Coulomb‐L'Herminé, Aurore; Perotti, Daniela; de Camargo, Beatriz; Bergeron, Christophe; et al.
Abstract : Clear cell sarcoma of the kidney (CCSK) although uncommon, is the second most frequent renal malignancy of childhood. Until now, the sole recurrent genetic aberration identified in CCSKs is t(10;17)(q22;p13), which gives rise to a fusion transcript of YWHAE and NUTM2B/E . So far, the clinical relevance of this fusion transcript is unknown. The aim of this descriptive study was to determine the clinical phenotype of t(10;17)(q22;p13) positive CCSKs. Snap‐frozen tissues, formalin‐fixed paraffin‐embedded tissues or RNA previously extracted from CCSK samples throughout European, North‐American and Japanese study groups were screened by RT‐PCR for the YWHAE‐NUTM2B/E transcript. Clinical characteristics, tumor characteristics, and outcome of patients with and without the fusion transcript were studied. The cohort comprised 51 previously published cases to which were added 139 internationally collected CCSK samples. RNA from 57 of these additionally collected cases was of sufficient quality to be successfully screened for the YWHAE‐NUTM2B/E transcript. In total, seven of the 108 cases harbored the fusion transcript. Patients with tumors containing the fusion transcript were relatively young (median age 10 months), had associated low median tumor volumes and stage I disease was not observed in these patients. Two of seven patients relapsed and one of seven patients died of disease. Ranges of values were not overtly different between patients with and without the fusion transcript; however, the number of fusion transcript positive cases turned out to be too small to permit reliable statistical analysis. The current study did not identify an explicit clinical phenotype of CCSK cases harboring the YWHAE‐NUTM2B/E fusion transcript. © 2015 Wiley Periodicals, Inc.